Simulasi Tes Figural Berbasis Game Untuk Melatih Kemampuan Dasar Akademik - Arin Yuli Astuti; S Sugianti; Ellisia Kumalasari (LPPM STIKOM Tunas Bangsa, 2022)
Informatics Engineering is one of the study programs at the Faculty of Engineering, University of Muhammadiyah Ponorogo. The output of graduate students is being able to code a program with fairly good reasoning analysis. Because to make a programming requires good logic so that the system / application can run. To determine class classification, it is necessary to have an academic potential test, especially figural simulations. The figural simulation tests that are made require more interesting innovations so students don't get bored. If the game designed is often played, students will be able to memorize various patterns of images. In measuring how effective this game will be useful, a trial will be carried out on 50 students. Trials were carried out before and after playing the games that were carried out. The standard limit of success must reach a predetermined score. If the value exceeds the number that has become the standard then it can be said that the player is able to logic an image. The test results before and after carrying out the figural test packaged in the form of a game will be synchronized in a conclusion and comparison. The results are assessed from the scores/numbers obtained and sharpness in the logic of a case.